Knowledge Assets, I-Market Platform Utilization, and Consumer Satisfaction of Micro and Small Enterprises in Indonesia - Nurul Haeriyah Ridwan; Ni Luh Sinta Yani; Moch Faizal Rachmadi (Universitas Negeri Semarang, 2026)
This study analyzes the influence of knowledge assets and I-Market platform utilization on consumer satisfaction of Micro and Small Enterprises (MSEs) in Indonesia. Data were collected through a survey of 140 MSE owners in Indonesia using a 1–5 Likert scale and analyzed using SEM- PLS (WarpPLS). The results show that knowledge assets and I-Market platform utilization have a positive and statistically significant effect on consumer satisfaction. The model explains 64% of the variance in consumer satisfaction, with I-Market utilization demonstrating a more dominant influence compared to knowledge assets. These findings emphasize the importance of a holistic approach that aligns human resource competency development with the acceleration of digital inclusion to build sustainable consumer loyalty within the digital economic ecosystem.